PENGARUH PENERAPAN INKUIRI TERBIMBING BERBANTUAN QUIPPER SCHOOL TERHADAP HASIL BELAJAR SISWA - Rita Maryanti; lisa utami (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2018)
This research is motivated by students less active participation and less interested in the learning process so that the low student learning outcomes are marked by the number of students who have not reached the Minimum Completion Criteria (in Indonesian: KKM). This research was a Quasi-experiment aiming at knowing the effect of using Guided Inquiry learning model with Quipper School toward student learning achievement at the tenth grade of State Senior High School 2 Pangkalan Kerinci.  Random sampling technique was used in this research. There were two sample classes, the tenth grade students of class MIPA 2 as the experimental group and MIPA 3 as the control group. ObservatiPon, test, and documentation were the techniques of collecting the data. t-test was used to find the research finding of student chemistry learning achievement. Based on the result of final data processed, it was obtained that tobserved was 2.79 and ttable was 1.66, it showed that tobserved was higher thanttable. It revealed that there was an effect toward learning achievement that Kp was 10.3%. Thus, it could be concluded that the use of Guided Inquiry learning model with Quipper School affected positively student learning achievement on Periodic System of the Elements material at the tenth grade of State Senior High School 2 Pangkalan Kerinci. Keywords: Guided Inquiry Learning Model, Quipper School, Learning Achievement, Periodic System of the Elements